In-utero infection with HIV-1 associated with suppressed lymphoproliferative responses at birth. (4th September 2014) - Lohman-Payne, B; Sandifer, T; OhAinle, M; Crudder, C; Lynch, J; Omenda, M M; Maroa, J; Fowke, K; John-Stewart, G C; Farquhar, C
Summary: In-utero exposure to HIV-1 may affect the immune system of the developing child and may induce HIV-1-specific immune responses, even in the absence of HIV-1 infection. We evaluated lymphoproliferative capacity at birth among 40 HIV-1-uninfected infants born to HIV-1-infected mothers and 10 infants who had acquired HIV-1 in utero . Cord blood mononuclear cells were assayed using [ 3 H]-thymidine incorporation for proliferation in response to HIV-1 p55- gag and the control stimuli phytohaemagglutinin (PHA), Staphylococcus enterotoxin B (SEB) and allogeneic cells. In response to HIV-1 p55-gag, eight (20%) HIV-1-exposed, uninfected (EU) infants had a stimulation index (SI) ≥ 2 and three (30%) in-utero HIV-1 infected infants had SI ≥2. The frequency and magnitude of responses to HIV-1 p55-gag were low overall, and did not differ statistically between groups. However, proliferative responses to control stimuli were significantly higher in EU infants than in infants infected in utero, with a median SI in response to PHA of 123 [interquartile range (IQR) 77–231] versus 18 (IQR 4–86) between EU and infected infants, respectively ( P < 0·001). Among infected infants, gestational maturity was associated with the strength of HIV-1 p55-gag response ( P < 0·001); neither maternal nor infant HIV-1 viral load was associated. In summary, EU and HIV-1-infected infants mounted HIV-1-specific lymphoproliferative responses at similar rates (20–30%), and although global immune function was preserved among EU infants, neonatal immune responses were significantly compromised by HIV-1 infection. Such early lymphoproliferative compromise may, in part, explain rapid progression to AIDS and death among HIV-1-infected infants.